Assessing the contribution of farmers’ working conditions to productive efficiency in the presence of uncertainty, a nonparametric approach - Ait Sidhoum, Amer (Springer Science and Business Media LLC, 2022)
This article investigates the contribution of farmers’ working conditions to production efficiency under state-contingent production uncertainty. Directional distance function is used to estimate efficiency scores and input shadow prices for 180 Spanish crop farms in 2015. Results suggest that shadow prices vary considerably between the different states of nature, suggesting why incorporating the stochastic production specification is important. The present study provides evidence of the important contribution of working conditions to technical efficiency. Thus, improved working conditions have the potential to help farms to progress toward sustainable agriculture.
Keywords: Data envelopment analysis; State-contingent approach; Shadow prices; Social sustainability; Working conditions